Ag-coated material, manufacturing method for Ag-coated material and terminal parts

A multi-layer AG film structure with varying crystal grain sizes and orientations addresses the heat-resistant adhesion and bending issues in electric vehicle contacts and terminal parts, enhancing durability and performance.

JP7625412B2Active Publication Date: 2025-02-03DOWA METALTECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020204658
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-10
Publication Date
2025-02-03
Estimated Expiration
2040-12-10

AI Technical Summary

Technical Problem

Existing materials for contacts and terminal parts in electric vehicles lack sufficient heat-resistant adhesion and bending properties, leading to potential peeling and reduced lifespan due to joule heat and bending stress.

Method used

A silver-coated material with a multi-layer AG film structure, featuring alternating layers with different average crystal grain sizes and orientations, is applied to enhance heat-resistant adhesion and bending properties.

Benefits of technology

The multi-layer AG film structure provides excellent heat-resistant adhesion and bending properties, preventing peeling and extending the lifespan of connectors and terminal parts in electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625412000002
    Figure 0007625412000002
  • Figure 0007625412000001
    Figure 0007625412000001
Patent Text Reader

Abstract

To provide an Ag coating material and a production method thereof in which heat-resistant adhesion and bending workability are excellent.SOLUTION: An Ag coating material and its related technique are provided. The Ag coating material includes a material and an Ag film formed on the surface of the material. The Ag film has at least three laminated Ag layers each of which has crystal grains three times or more different in average size, which are laminated alternately.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Ag-coated material and a manufacturing method thereof, and in particular to an Ag-coated material used as a material for contacts and terminal parts such as connectors, switches, and relays used in automotive and consumer electrical wiring, and a manufacturing method thereof. [Background technology]

[0002] Conventionally, as materials for contacts and terminal parts of connectors and switches, plated materials have been used in which relatively inexpensive materials such as copper, copper alloys, and stainless steel, which are excellent in corrosion resistance and mechanical properties, are plated with tin, silver, gold, etc. depending on required properties such as electrical properties and solderability. Metal films formed by plating have excellent adhesion to materials, and plating has the advantage of low manufacturing costs.

[0003] Tin-plated products, which are obtained by plating copper or copper alloys, stainless steel, and other materials with tin, are inexpensive but have poor corrosion resistance in high-temperature environments. Gold-plated products, which are obtained by plating these materials with gold, have excellent corrosion resistance and high reliability, but the raw material costs are high. On the other hand, silver-plated products, which are obtained by plating these materials with silver, are inexpensive compared to gold-plated products and have excellent corrosion resistance compared to tin-plated products.

[0004] Furthermore, materials for contacts and terminal parts of connectors, switches, etc. are required to have wear resistance associated with insertion and removal of connectors and sliding of switches.

[0005] Patent Document 1 discloses that an Ag-plated material having a surface layer made of Ag plating with a preferred orientation plane of {111} on a base material can prevent an increase in contact resistance while maintaining high hardness (wear resistance).The same document discloses that it is preferable to form an underlayer made of nickel between the base material and the surface layer, and that this underlayer can increase the adhesion between the base material and the surface layer.

[0006] In addition, terminals and the like are often punched out into a desired shape using a press process using Ag-plated material, and then bent to form the product shape. However, during this bending process, cracks may occur, causing the material to break, or cracks may occur that expose the material, causing it to corrode, and this may significantly shorten the product's lifespan.

[0007] Regarding such bending workability, Patent Document 2 discloses a silver-plated product in which a surface layer made of silver is formed on the surface of a base material made of copper or a copper alloy, or on the surface of a base layer made of copper or a copper alloy formed on a base material, and in which the ratio of the X-ray diffraction intensity of the {200} plane to the sum of the X-ray diffraction intensities of the {111} plane, {200} plane, {220} plane, and {311} plane of the surface layer is 40% or more. The document discloses that this silver-plated product has good bending workability and can suppress an increase in contact resistance even when used in a high-temperature environment.

[0008] Patent Document 3 discloses a silver-plated laminate which is a laminate of a metal substrate and a silver-plated layer, the silver-plated layer having a soft silver-plated layer formed on the surface of the metal substrate and a hard silver-plated layer formed on the surface of the soft silver-plated layer, and the Vickers hardness of the soft silver-plated layer is at least 30 HV lower than the Vickers hardness of the hard silver-plated layer. It also discloses that this silver-plated laminate has both excellent abrasion resistance and processability.

[0009] Patent Document 4 discloses that the contact portion of the contact has a base material made of copper or a copper alloy, a second plating layer formed on the base material, and a first plating layer formed on the second plating layer, the first plating layer being made of silver or a silver alloy and having a Vickers hardness of 90 Hv or less, and the second plating layer being made of silver or a silver alloy and having a Vickers hardness of 100 Hv or more. The document discloses that a connector equipped with such a contact has low contact resistance. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2015-110833 A [Patent Document 2] JP 2013-76127 A [Patent Document 3] JP 2014-95139 A [Patent Document 4] JP 2016-15224 A Summary of the Invention [Problem to be solved by the invention]

[0011] As described above, materials for contacts, terminal components, and the like are required to have properties such as wear resistance and bending workability.

[0012] Incidentally, in recent years, the need for electric vehicles such as EVs (Electric Vehicles) and PHVs (Plug-in Hybrid Vehicles) has been increasing due to issues with environmental regulations. For the materials of the contacts and terminal parts of electric vehicles, drawn copper materials coated with a layer of silver are often used as the base material from the viewpoint of electrical conductivity and contact reliability.

[0013] In electric vehicles, taking into consideration the usage environment (such as Joule heat generation due to current flow), excellent heat-resistant adhesion is required between the material and the silver layer, or between the base Ni layer and the silver layer.Specifically, there is a challenge to prevent peeling between the base material and the silver layer, or between the nickel layer and the silver layer, when connectors with silver layers are heated in a contact (fitted) state and then separated.

[0014] None of the configurations disclosed in Patent Documents 1 to 4 have sufficient heat-resistant adhesion, and the configurations disclosed in Patent Documents 1 and 4 also have sufficient bending workability.

[0015] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a silver-coated material having excellent heat-resistant adhesion and bending workability, and a method for producing the same. [Means for solving the problem]

[0016] The first aspect of the present invention is A material and an Ag-coated material having an Ag coating formed on the material, The Ag coating is an Ag-coated material characterized in having at least three Ag layers alternately laminated together, the Ag layers having average crystal grain sizes that differ by three times or more.

[0017] A second aspect of the present invention is the method according to the first aspect, The Ag coating is characterized by having four or more laminated Ag layers.

[0018] A third aspect of the present invention is the first or second aspect of the present invention, The Ag coating is characterized by having an Ag layer in which, from the side closer to the material, an Ag layer 1 made of Ag with a small average crystal grain size and an Ag layer 2 made of Ag with a larger average crystal grain size than that of Ag layer 1 are alternately laminated.

[0019] A fourth aspect of the present invention is the third aspect, The Ag layer 1 is characterized in that its average crystal grain size (area average grain size) is 0.2 μm or less.

[0020] A fifth aspect of the present invention is the third or fourth aspect, The Ag layer 2 is characterized in that its average crystal grain size (area average grain size) is 0.3 μm or more.

[0021] A sixth aspect of the present invention is the aspect according to any one of the third to fifth aspects, The Ag layer 1 has a thickness of 0.5 to 5 μm.

[0022] A seventh aspect of the present invention is an aspect according to any one of the third to sixth aspects, The Ag layer 2 has a thickness of 0.5 to 5 μm.

[0023] An eighth aspect of the present invention is an aspect according to any one of the third to seventh aspects, The preferred orientation plane of the Ag layer 1 is a {111} plane, and the preferred orientation plane of the Ag layer 2 is a {100} plane.

[0024] A ninth aspect of the present invention is the aspect according to any one of the third to eighth aspects, The Ag-coated material is characterized in that the outermost layer thereof is constituted by the Ag layer 2.

[0025] A tenth aspect of the present invention is the aspect according to any one of the first to ninth aspects, The present invention is characterized in that a base layer made of Ni is formed between the material and the Ag coating.

[0026] An eleventh aspect of the present invention is the aspect according to any one of the first to tenth aspects, The material is characterized in that it is made of Cu or a Cu alloy.

[0027] A twelfth aspect of the present invention is the aspect according to any one of the first to eleventh aspects, The Ag-coated material is characterized in that its Vickers hardness HV is 100 or more.

[0028] A thirteenth aspect of the present invention is a method for producing a composition comprising the steps of: This is a method for producing an Ag-coated material, characterized in that an Ag coating is formed on a material by alternately laminating at least three Ag layers, each layer having an average crystal grain size that differs by a factor of three or more.

[0029] A fourteenth aspect of the present invention is the thirteenth aspect, The Ag coating is characterized in that four or more of the Ag layers are laminated.

[0030] A fifteenth aspect of the present invention is the thirteenth or fourteenth aspect, On the material, The Ag layer 1 made of Ag having a small average crystal grain size and the Ag layer 2 made of Ag having a larger average crystal grain size than the Ag layer 1 are alternately formed.

[0031] A sixteenth aspect of the present invention is the fifteenth aspect, The Ag layer 1 is characterized in that its average crystal grain size (area average grain size) is 0.2 μm or less.

[0032] A seventeenth aspect of the present invention is the fifteenth or sixteenth aspect, The Ag layer 2 is characterized in that its average crystal grain size (area average grain size) is 0.3 μm or more.

[0033] An 18th aspect of the present invention is an aspect according to any one of the 15th to 17th aspects, The Ag layer 1 has a thickness of 0.5 to 5 μm.

[0034] A 19th aspect of the present invention is an aspect according to any one of the 15th to 18th aspects, The Ag layer 2 has a thickness of 0.5 to 5 μm.

[0035] A twentieth aspect of the present invention is an aspect according to any one of the fifteenth to nineteenth aspects, The preferred orientation plane of the Ag layer 1 is a {111} plane, and the preferred orientation plane of the Ag layer 2 is a {100} plane.

[0036] A 21st aspect of the present invention is an aspect according to any one of the 15th to 20th aspects, The Ag layer 2 is formed as the outermost layer of the Ag-coated material.

[0037] A 22nd aspect of the present invention is an aspect according to any one of the 15th to 21st aspects, The Ag layer 1 is Using Ag plating solution 1 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate, the solution temperature is 10 to 35°C, and the current density is 3 to 15 A / dm 2 The film is formed by electroplating under the following conditions: The Ag plating solution 1 is 80-130g / L silver, 60-160g / L potassium cyanide; It is characterized in that it is an aqueous solution containing 50 to 80 mg / L of selenium.

[0038] A twenty-third aspect of the present invention is the twenty-second aspect, The selenium content is 55 to 70 mg / L.

[0039] A 24th aspect of the present invention is the 22nd or 23rd aspect of the present invention, The product of the concentration of potassium cyanide in the Ag plating solution 1 and the current density is 840 g A / L dm 2 The electroplating is carried out under the following conditions:

[0040] A 25th aspect of the present invention is an aspect according to any one of the 15th to 24th aspects, The Ag layer 2 is Silver plating solution 2 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate was used, and the solution temperature was 10 to 40°C and the current density was 3 to 10 A / dm 2 The resulting product is formed by electroplating with The silver plating solution 2 is 80-110g / L silver, 70-160g / L potassium cyanide; It is characterized in that it is an aqueous solution containing 1 to 15 mg / L of selenium.

[0041] A 26th aspect of the present invention is an aspect according to any one of the 13th to 25th aspects, The method is characterized in that a base layer made of Ni is formed on the material, and the Ag coating is formed on the base layer.

[0042] A 27th aspect of the present invention is an aspect according to any one of the 13th to 26th aspects, The material is characterized in that it is made of Cu or a Cu alloy.

[0043] A 28th aspect of the present invention is a method for producing a composition comprising the steps of: A terminal part using the Ag-coated material according to any one of the first to twelfth aspects as a constituent material. Effect of the Invention

[0044] The present invention can provide a silver-coated material having excellent heat-resistant adhesion and bending workability, and a method for producing the same. [Brief description of the drawings]

[0045] [Figure 1] FIG. 1 is a photograph showing a SIM (scanning ion microscope) image of a cross section of the Ag-coated material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] Hereinafter, the present embodiment will be described. In this specification, "to" indicates a predetermined value or more and a predetermined value or less. Hereinafter, the embodiment of the Ag-coated material and the manufacturing method thereof of the present invention will be described.

[0047] [Ag-coated material] Hereinafter, each configuration of the embodiment of the Ag-coated material of the present invention will be described.

[0048] <Material> An embodiment of the Ag-coated material of the present invention has a material and an Ag film formed on the material. As the material, those conventionally used as materials for materials such as contact or terminal parts can be widely adopted. From the viewpoints of corrosion resistance and mechanical properties, a material formed of Cu (copper), a Cu alloy, or stainless steel is preferable, and from the viewpoint of conductivity in addition to the above points, a material formed of Cu or a Cu alloy is preferable. The Cu alloy preferably contains 90% by mass or more of Cu, and other metal elements constituting the Cu alloy include Ni, Sn, P, Si, Co, Fe, Mg, Zn, Ti, and the like.

[0049] <Ag film> The Ag film formed on the material is characterized by having an Ag layer in which at least three Ag layers with an average crystal grain size different by three times or more are alternately laminated. Furthermore, it preferably has an Ag layer laminated with four or more layers.

[0050] The above "the average crystal grain size is different by three times or more" means that in adjacent Ag layers with different average crystal grain sizes, when the average crystal grain size of the Ag layer with a larger average crystal grain size (referred to as D2) is divided by the average crystal grain size of the Ag layer with a smaller average crystal grain size (referred to as D1), it is 3 or more, that is, D2 / D1≥3. The Ag layer in which three Ag layers with an average crystal grain size different by three times or more are alternately laminated means that an Ag layer with a smaller average crystal grain size (average crystal grain size = D1a), an Ag layer with a larger average crystal grain size (average crystal grain size = D2), and an Ag layer with a smaller average crystal grain size (average crystal grain size = D1b) are laminated in order, and both D2 / D1a and D2 / D1b are 3 or more. The above lamination order may be in the order of an Ag layer with a larger average crystal grain size, an Ag layer with a smaller average crystal grain size, and an Ag layer with a larger average crystal grain size.

[0051] Also, the Ag film preferably has an Ag layer in which an Ag layer 1 made of Ag with a smaller average crystal grain size and an Ag layer 2 made of Ag with an average crystal grain size (three times or more) larger than that of Ag layer 1 are alternately laminated from the side closer to the material.

[0052] The Ag coating formed on the material (or the undercoat layer described later) is preferably a four-layer laminate consisting of two layers of Ag layer 1 and two layers of Ag layer 2, which are layers made of Ag (silver) having a predetermined preferred orientation plane. Note that Ag layers that are difficult to distinguish as multiple Ag layers because of their very thin thickness (for example, Ag layers with a very small thickness such as the Ag strike plating layer described later, for example, Ag layers with a thickness of 0.1 μm or less) are not counted as multiple layers.

[0053] (Ag layer 1) The Ag layer 1 is a layer made of Ag having a smaller average crystal grain size than the Ag layer 2 described below. The average crystal grain size (area average grain size) of the Ag layer 1 is preferably 0.005 μm or more, and more preferably 0.2 μm or less, and further preferably 0.15 μm or less.

[0054] In addition, the Ag layer 1 is preferably composed of Ag having a {111} plane as a preferred orientation plane. The preferred orientation plane is a crystal plane corresponding to the diffraction peak with the highest intensity among the 111 diffraction peak, the 200 diffraction peak, the 110 diffraction peak, and the 311 diffraction peak when the surface of the Ag layer 1 is subjected to X-ray diffraction analysis. Details of how to determine the preferred orientation plane will be described later in the examples.

[0055] The Ag layer 1 is believed to have a high hardness, which contributes to the excellent wear resistance of the Ag-coated material of the present invention.

[0056] The thickness of the Ag layer 1 is not particularly limited, but from the viewpoints of its function, cost and bending workability, it is preferably 0.5 to 5 μm, and more preferably 0.7 to 3 μm.

[0057] The Ag layer 1 may contain, for example, 1.0 mass % or less, or 0.5 mass % or less of elements such as Se and Sb and inevitable impurities. From the viewpoint of electrical conductivity, the Ag layer 1 preferably contains 99.9 mass % or more of Ag.

[0058] (Ag layer 2) The Ag layer 2 is a layer made of Ag having an average crystal grain size three or more times (preferably four or more times, and more preferably five or more times) larger than that of the Ag layer 1. The average crystal grain size (area average grain size) of this Ag layer 2 is preferably 0.3 μm or more, more preferably 0.4 μm or more, and is preferably 1.0 μm or less.

[0059] It is preferable that the difference between the average crystal grain size of the Ag layer 2 and the average crystal grain size of the Ag layer 1 is a predetermined value or more (or within a predetermined range). For example, the difference is preferably 0.2 μm or more, more preferably 0.3 μm or more, and is preferably 2 μm or less, more preferably 1 μm or less.

[0060] Moreover, the surface of the Ag layer 2 constituting the Ag coating is preferably composed of Ag whose preferred orientation plane is the {100} plane.

[0061] The Ag layer 2 is easily deformed when subjected to bending, and contributes to the excellent bending workability of the Ag-coated material of the present invention.

[0062] The thickness of the Ag layer 2 is not particularly limited, but from the viewpoints of its function, cost and bending workability, it is preferably 0.5 to 5 μm, and more preferably 0.7 to 3 μm.

[0063] The Ag layer 2 may contain, for example, 1.0 mass % or less, or 0.5 mass % or less of elements such as Se and Sb and inevitable impurities. From the viewpoint of electrical conductivity, the Ag layer 1 preferably contains 99.9 mass % or more of Ag.

[0064] (Stacking of Ag layer 1 and Ag layer 2) The Ag coating is a laminate formed by alternately laminating the above-described Ag layer 1 and Ag layer 2. It is believed that the above-described laminate provides superior heat-resistant adhesion to the base material (or the underlayer described later) compared with a plating layer that is a single layer of either the Ag layer 1 or the Ag layer 2, and is less susceptible to peeling between the Ag coating and the base material (or the underlayer described later).

[0065] Regarding bending workability, it is considered that the cracks are generated when the starting point of the cracks is generated at any one of the layers in the Ag coating during bending work, and the cracks extend vertically (crack propagation) and penetrate vertically. When the Ag-coated material is bent, it is considered that the layer farther from the material (closer to the surface) among the constituent layers of the Ag coating has a larger tensile stress and is more likely to cause the starting point of the cracks. In the present invention, since the Ag coating is a laminate of three or more Ag layers, preferably four or more Ag layers, the propagation of the cracks is stopped at the interface between the layers, which is considered to contribute to the excellent bending workability of the Ag-coated material of the present invention.

[0066] The excellent heat-resistant adhesion and bending workability described above cannot be exhibited by a laminate consisting of one Ag layer 1 and one Ag layer 2, totaling two layers; to exhibit these effects, a laminate consisting of three or more layers, preferably four or more layers, is required.

[0067] Specific examples of the laminated structure of the Ag layers 1 and 2 in the Ag coating described above, including the positional relationship with the material (underlayer), are as follows: Material (base layer)-Ag layer 1-Ag layer 2-Ag layer 1-Ag layer 2 Material (base layer) - Ag layer 2 - Ag layer 1 - Ag layer 2 - Ag layer 1 It is preferable that the outermost layer of the Ag-coated material is composed of the Ag layer 2.

[0068] There is no limitation on the thickness ratio of Ag layer 1 to Ag layer 2, but it is preferable that 0.5≦(thickness of Ag layer 1 / thickness of Ag layer 2)≦5.0.

[0069] <Other layers> The embodiment of the Ag-coated material of the present invention has the material and Ag coating described above, and may further have other layers depending on the purpose.

[0070] For example, particularly when the material is made of Cu or a Cu alloy, in order to prevent the Cu and alloy components in the material from diffusing into the Ag film and deteriorating the heat resistance, it is desirable that an underlayer made of Ni (nickel) is formed between the material and the Ag film. The thickness of the underlayer is not particularly limited, but from the viewpoints of its function and cost, it is preferably 0.3 to 2 μm, and more preferably 0.5 to 1.5 μm.

[0071] For example, when manufacturing an Ag-coated material by the manufacturing method of the Ag-coated material described later, a very thin intermediate layer made of Ag may be formed between the material or the base and the Ag film.

[0072] <Vickers hardness of Ag-coated material> The Vickers hardness of the Ag-coated material of the present invention is preferably 98 or more, and more preferably 100 or more (unit: kgf / mm 2 ). Note that if the hardness is too high, it may adversely affect the bendability, so the Vickers hardness is preferably 135 or less.

[0073] The Vickers hardness of the Ag-coated material is the Vickers hardness measured on the surface of the Ag-coated material, and the surface refers to the surface of the portion of the Ag-coated material where the Ag film is formed. Details of the method for measuring the Vickers hardness will be described later in the examples.

[0074] <Method for confirming Ag layers 1 and 2 in Ag film> In the Ag-coated material of the present invention, the fact that the Ag film has the above-described configuration (crystal grain size, preferred orientation plane, etc.) can be confirmed by, for example, the following method.

[0075] First, the fact that the Ag film has a three-layer or more configuration can be confirmed by creating a cross-sectional sample perpendicular to the surface of the Ag-coated material and observing this sample with a scanning microscope, a scanning ion microscope, or the like. Since Ag layer 1 has a smaller crystal grain size than Ag layer 2, it can be distinguished by the size of the crystal grain size.

[0076] In addition, the surface of the Ag coating material can be analyzed by X-ray diffraction (XRD) or EBSD (Electron BackScatter Diffraction Pattern) analysis method to determine the preferred orientation plane of the outermost layer of the Ag film. Next, the outermost layer is removed by a known method (such as polishing, milling, sputtering, etching, etc.), and for the second layer from the top, the preferred orientation plane is similarly determined. By repeating this, it can be confirmed that the Ag film has a structure of three or more layers of Ag layers 1 and 2 defined in the present invention.

[0077] [Method for manufacturing Ag-coated material] Next, embodiments of the method for manufacturing the Ag-coated material of the present invention will be described.

[0078] In this manufacturing method, at least three layers of Ag layers with significantly different average crystal grain sizes (by a factor of 3 or more) are alternately laminated on a material to form an Ag film. It is preferable to laminate four or more layers of the Ag layers to form the Ag film.

[0079] Also, it is preferable that a manufacturing method forms an Ag film composed of three or more Ag layers by alternately forming an Ag layer 1 made of Ag with a small average crystal grain size and an Ag layer 2 made of Ag with an average crystal grain size 3 times or more larger than that of Ag layer 1 on a material. Furthermore, it is preferable to form an Ag-coated material with the preferred orientation plane of Ag layer 1 being the {111} plane and the preferred orientation plane of Ag layer 2 being the {100} plane. The material is the same as that described above for the embodiments of the Ag-coated material of the present invention.

[0080] [Ag film] As described above, the Ag film is composed of three or more Ag layers in which Ag layer 1 and Ag layer 2 are alternately laminated. Ag layer 1 and 2 are the same as those described above for the embodiments of the Ag-coated material of the present invention. Hereinafter, the formation methods of Ag layer 1 and 2 will be described. Before forming the Ag film, the material with an underlying layer formed thereon as needed may be pretreated (such as electrolytic degreasing or pickling).

[0081] [Formation of Ag layer 1] The Ag layer 1 can be formed by a known method (for example, the method disclosed in Patent Document 1). The Ag layer 1 is preferably formed by plating from the viewpoints of the material, adhesion to the underlayer or Ag layer 2, and manufacturing costs.

[0082] More specifically, Ag plating solution 1 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate is used, and the solution temperature is 10 to 35°C, the current density is 3 to 15 A / dm 2 It is preferable to form the Ag layer 1 by electroplating (on the material, underlayer or Ag layer 2) under the above conditions. The Ag plating solution 1 is an aqueous solution containing 80 to 130 g / L (preferably 80 to 110 g / L) of silver, 60 to 160 g / L (preferably 70 to 160 g / L) of potassium cyanide, and 50 to 80 mg / L (preferably 55 to 70 mg / L) of selenium. (Note that potassium silver cyanide and potassium selenocyanate generate cyanide ions and potassium ions when ionized, but these are not included in the concentration of potassium cyanide.) When electroplating is performed using an Ag plating solution with such a high selenium concentration, a silver layer whose preferred orientation plane is the {111} plane can be suitably formed. In addition, from the viewpoint of suitably forming a silver layer whose preferred orientation plane is the {111} plane, this electroplating is performed under the following conditions: the product of the concentration of potassium cyanide in the Ag plating solution 1 and the current density is 840 g·A / L·dm 2 From the same viewpoint, it is preferable to carry out the test under the condition that the product is 250g A / L dm 2 It is preferable to carry out the process under the above conditions.

[0083] The Ag plating solution 1 may be an aqueous solution containing 74 to 203 g / L of potassium silver cyanide, 70 to 160 g / L of potassium cyanide, and 73 to 128 mg / L of potassium selenocyanate.

[0084] (Formation of Ag layer 2) The Ag layer 2 can be formed by a known method (for example, the method disclosed in Patent Document 2). The Ag layer 2 is preferably formed by plating from the viewpoints of the material, adhesion to the underlayer or Ag layer 1, and manufacturing costs.

[0085] More specifically, a silver plating solution 2 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate is used, and the solution temperature is 10 to 40° C., the current density is 3 to 10 A / dm 2 It is preferable to form the Ag layer 2 by electroplating (on the material, underlayer or Ag layer 1) under the above conditions. The silver plating solution 2 is an aqueous solution containing 80 to 110 g / L of silver, 70 to 160 g / L of potassium cyanide, and 1 to 15 mg / L of selenium. (Note that potassium silver cyanide and potassium selenocyanate generate cyanide ions and potassium ions when ionized, but these are not included in the concentration of potassium cyanide.) When electroplating is performed using an Ag plating solution containing such a small amount of selenium, a silver layer whose preferred orientation plane is the {100} plane can be suitably formed.

[0086] The Ag plating solution 1 may be an aqueous solution containing 74 to 203 g / L of potassium silver cyanide, 70 to 160 g / L of potassium cyanide, and 3 to 30 mg / L of potassium selenocyanate.

[0087] (Average grain size) The specific manufacturing method of the Ag layer 1 and the Ag layer 2 as described above can provide a manufacturing method for forming an Ag coating composed of three or more Ag layers by alternately forming, on a material, an Ag layer 1 made of Ag with a small average crystal grain size and an Ag layer 2 made of Ag with an average crystal grain size larger than that of the Ag layer 1. In this case, when the average crystal grain size of the Ag layer 1 is D1 and the average crystal grain size of the Ag layer 2 is D2, D2 / D1≧3.

[0088] It is also possible to provide a method for producing an Ag-coated material in which the average crystal grain size (area average grain size) of the Ag layer 1 is 0.2 μm or less and the average crystal grain size (area average grain size) of the Ag layer 2 is 0.3 μm or more.

[0089] The Ag layer 1 preferably has a thickness of 0.5 to 5 μm, and the Ag layer 2 preferably has a thickness of 0.5 to 5 μm.

[0090] (Ag strike plating) Before forming an Ag film on the base material or underlayer, it is preferable to form a very thin intermediate layer by Ag strike plating to improve adhesion between the base material or underlayer and the Ag film.

[0091] <Other layers> As described above in the description of the embodiment of the Ag-coated material, in the present invention, other layers (such as an underlayer made of nickel) may be formed in addition to the material and the Ag coating.

[0092] When forming an underlayer made of nickel on a base material, any known method can be used as a method for forming the underlayer without any particular restrictions, and from the standpoint of adhesion to the base material and cost, an electroplating method is preferred.

[0093] Furthermore, when emphasis is placed on wear resistance in the Ag-coated material to be manufactured, it is preferable to form Ag layer 1 (formed by the same method as above) as the outermost layer, and when emphasis is placed on bending workability, it is preferable to form Ag layer 2 (formed by the same method as above) as the outermost layer.

[0094] [Terminal parts] The Ag-coated material manufactured by the embodiment of the Ag-coated material and the embodiment of the manufacturing method of the Ag-coated material of the present invention described above has excellent heat resistance, adhesion, bending workability, and abrasion resistance, and is therefore suitable as a constituent material for contacts and terminal parts.

[0095] The technical scope of the present invention is not limited to the above-described embodiments, but also includes forms in which various modifications and improvements are made within the scope that can derive specific effects obtained by the constituent elements of the invention and their combinations.

[0096] For example, in this embodiment, the Ag coating has an Ag layer in which Ag layers 1 and Ag layers 2 are alternately stacked in pairs from the side closer to the material. On the other hand, at least three layers may be stacked as long as Ag layers with different average crystal grain sizes are alternately stacked. For example, Ag layer 1, Ag layer 2, and Ag layer 1 may be stacked from the side closer to the material, or Ag layer 2, Ag layer 1, and Ag layer 2 may be stacked. The Ag coating may also have four or more Ag layers. For example, Ag layer 1, Ag layer 2, Ag layer 1, Ag layer 2, Ag layer 1, and Ag layer 2 may be stacked from the side closer to the material, or Ag layer 2, Ag layer 1, Ag layer 2, Ag layer 1, Ag layer 2, and Ag layer 1 may be stacked. EXAMPLES

[0097] The present invention will now be described in detail with reference to examples. The present invention is not limited to the following examples. Note that the contents not described below are the same as those described in the present embodiment.

[0098] EXAMPLES Hereinafter, examples of the silver-plated product and the manufacturing method thereof according to the present invention will be described in detail.

[0099] [Example 1] (Pretreatment: electrolytic degreasing and pickling) First, a rolled plate of pure copper (C1020) measuring 67 mm x 50 mm x 0.3 mm was prepared as the material (material to be plated). This material to be plated and the SUS plate were placed in an alkaline degreasing solution, and with the material to be plated as the cathode and the SUS plate as the anode, electrolytic degreasing was performed at a voltage of 5 V for 30 seconds. The material was then rinsed with water for 15 seconds, pickled in a 3% aqueous sulfuric acid solution for 15 seconds, and finally rinsed with water for 15 seconds.

[0100] (Ni plating) Next, in a nickel plating solution consisting of an aqueous solution containing 25 g / L of nickel chloride, 35 g / L of boric acid, and 540 g / L of nickel sulfamate tetrahydrate, the pretreated plated material was used as the cathode and the SK nickel electrode plate as the anode, and the plating was conducted at a current density of 7 A / dm at a solution temperature of 55°C while stirring at 500 rpm with a magnetic stirrer. 2Under the above conditions, electroplating (nickel plating) was performed until a thickness of 1 μm was reached to form a base layer made of nickel, and then the plate was washed with water for 15 seconds.

[0101] (Ag strike plating) Next, in an Ag strike plating solution consisting of an aqueous solution containing 3 g / L of silver potassium cyanide and 90 g / L of potassium cyanide, the plated material on which the undercoat layer was formed was used as the cathode, and a platinum-coated titanium electrode plate was used as the anode, and the plating was performed at a solution temperature of 18°C ​​and a current density of 2 A / dm while stirring at 500 rpm with a stirrer. 2 After electroplating (silver strike plating) for 10 seconds under the above conditions, the plate was rinsed with water for 15 seconds.

[0102] (Ag plating process A) Next, in an Ag plating solution consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2) (silver concentration 95 g / L), 95 g / L potassium cyanide (KCN), and 55 mg / L Se (selenium), the Ag strike-plated plated material was used as the cathode, and an Ag electrode plate consisting of Ag with a purity of 99.99 mass% or more was used as the anode, while stirring at 500 rpm with a stirrer at a liquid temperature of 18°C ​​and a current density of 5 A / dm 2 Under these conditions, electroplating (Ag plating) was performed until the thickness of the Ag plating film reached 1.25 μm, followed by rinsing with water for 15 seconds and drying with air pressure from an air gun to obtain a plated material on which a first Ag plating film (layer) was formed. Note that this Ag plating process is referred to as the "Ag plating process A" in the present specification. Note that Se in the Ag plating solution was supplied by adding potassium selenocyanate.

[0103] (Evaluation of crystal orientation) The surface of the first Ag plating film thus obtained was evaluated by an X-ray diffraction analyzer (Rigaku Corporation's fully automatic multipurpose horizontal X-ray diffraction analyzer Smart Lab) using a Cu tube and a Kβ filter method. From the X-ray diffraction pattern obtained by scanning in the 2θ range of 5 to 120 deg and at a scanning speed of 50 deg / min, the X-ray diffraction peak intensities (intensities of X-ray diffraction peaks) of the 111 diffraction peak, 200 diffraction peak, 220 diffraction peak, and 311 diffraction peak of the Ag plating film were divided by the relative intensity ratios (relative intensity ratios at the time of powder measurement) (111:200:220:311=100:40:25:26) listed in the JCPDS card No. 40783 to obtain a corrected value (corrected intensity). The crystal plane corresponding to the X-ray diffraction peak with the strongest corrected intensity was determined as the preferred orientation plane of the first Ag plating film. As a result, the preferred orientation plane was the {111} plane.

[0104] (Ag plating process B) Next, in a silver plating solution consisting of an aqueous solution containing 175 g / L potassium silver cyanide (KAg(CN)2) (silver concentration 95 g / L), 95 g / L potassium cyanide (KCN), and 6 mg / L Se (selenium), the plated material on which the first layer of Ag plating film was formed was used as the cathode, and an Ag electrode plate made of Ag with a purity of 99.99 mass% or more was used as the anode, and the solution was stirred at 500 rpm with a stirrer at a liquid temperature of 18°C ​​and a current density of 5 A / dm 2 Under the above conditions, electroplating (Ag plating) was performed until the thickness of the Ag plating film reached 1.25 μm, after which the plated material was rinsed with water for 15 seconds and dried with air pressure from an air gun to obtain a plated material on which a second Ag plating film (layer) was formed.

[0105] In the present specification, this Ag plating step is referred to as "Ag plating step B." Se in the Ag plating solution was supplied by adding potassium selenocyanate.

[0106] In addition, the results of X-ray diffraction evaluation of the Ag plating film produced under similar conditions in Comparative Example 2 described later showed that the preferred orientation plane of the second Ag plating film in this step was the {100} plane.

[0107] (Ag plating process A (2nd time)) Next, the sample on which the second layer of Ag plating film was formed was used as the plated material, and electroplating (Ag plating) was performed in the same manner as in the "Ag plating process A", followed by rinsing with water for 15 seconds to obtain a plated material on which a third layer of Ag plating film was formed.

[0108] (Ag plating process B (2nd time)) Next, the sample on which the third Ag plating film was formed was used as the plated material, and electroplating (Ag plating) was performed in the same manner as in the "Ag plating process B" described above. Thereafter, the sample was rinsed with water for 15 seconds and dried with air pressure from an air gun to obtain a plated material on which a fourth Ag plating film was formed (i.e., an Ag-coated material).

[0109] In this way, an Ag-coated material was obtained having four Ag plating layers, each of which was 1.25 μm thick, for a total thickness of 5 μm. The Ag purity (concentration) of each of these Ag plating layers was 99.9 mass% or more.

[0110] The Ag-coated materials were evaluated for the crystal grain size of the cross section of each Ag layer, bending workability, heat-resistant adhesion, Vickers hardness, contact resistance, and wear resistance.

[0111] FIG. 1 is a photograph showing a SIM (scanning ion microscope) image of a cross section of the Ag-coated material of Example 1. As shown in Figure 1, from the bottom, the following can be seen: the material, the Ni plating layer, the first Ag plating film from Ag plating process A, the second Ag plating film from Ag plating process B, the third Ag plating film from Ag plating process A, and the fourth Ag plating film from Ag plating process B. The Ag strike plating layer is thin, so it is difficult to see in Figure 1.

[0112] (crystal grain size) The Ag-coated material was cut, and the cross section was subjected to EBSD analysis to measure the average crystal grain size (area average grain size). More details are as follows: The cross section of the Ag-coated material was milled to a mirror surface using a cross-section polisher (IB-09010CP manufactured by JEOL Ltd.). This cross section was subjected to EBSD measurement using a field emission Auger microprobe (JAMP-9500F manufactured by JEOL Ltd.) equipped with an EBSD analyzer (OIM Analysis manufactured by TSL Solutions Co., Ltd.) at an acceleration voltage of 15 kV, a magnification of 20,000 times, a measurement field of view of 5.0 μm × 10.0 μm, and a step size of 20 nm. From the measurement results, an inverse pole figure (IPF) map was created using data collection software (OIM-DC, manufactured by TSL Solutions Co., Ltd.) and data analysis software (OIM, manufactured by TSL Solutions Co., Ltd.). Based on this IPF map, except for measurement points where the confidence index (CI value) analyzed by the above-mentioned data analysis software was 0.1 or less, boundaries where the crystal orientation difference between adjacent pixels was 5° or more were regarded as grain boundaries, and the average crystal grain size (area average grain size) was calculated based on the Area Fraction method using the above-mentioned data analysis software. As a result, the average crystal grain size (area average grain size) values, from the side closest to the substrate, were 0.080 μm in the first layer, 0.420 μm in the second layer, 0.080 μm in the third layer, and 0.563 μm in the fourth layer. In other words, the ratio of the average crystal grain sizes of adjacent Ag-plated layers was 3 or more.

[0113] (Bending workability) The bending workability of the Ag-coated material was evaluated by bending the Ag-coated material 90 degrees in the direction perpendicular to the rolling direction of the material at two levels of bending radius R = 1.0 mm and R = 0.5 mm according to the V-block method of JIS Z2248, and then observing the bent portion with a microscope (Keyence Corporation digital microscope VHX-1000) at 500 times magnification, based on whether or not the base material (Ni plating or Cu material) was exposed at the bent portion (mountain fold portion). The bending radius R is the radius of the curved portion of the pusher that presses against the Ag-coated material to bend it, and the value R / t obtained by dividing the bending radius R by the plate thickness t is 3.3 (when R = 1.0) and 1.67 (when R = 0.5), respectively.

[0114] As a result, no exposure of the base material was observed regardless of the bending radius, and bending workability was good.

[0115] (Heat-resistant adhesion) Two test pieces (50mm x 10mm) were cut out from this Ag-coated material, one of which was made into a flat test piece, and the other was embossed (hemispherical stamping with inner R = 1.5mm) to make an embossed test piece (indenter), and the convex part of the embossed test piece was brought into contact with the flat test piece, and then the two were clamped and fixed with a paper clip (TANOSEE paper clip large size 28mm, model TG-2G), placed in a constant temperature bath (constant temperature bath OF-450 manufactured by AS ONE Corporation) at 200°C for 120 hours, then removed, the paper clip was removed, and the two test pieces were separated. Three sets of such test pieces were made and evaluated.

[0116] The contact area between the separated flat test piece and the embossed test piece was observed using a microscope (Keyence Corporation's shape analysis laser microscope VK-X150) with an objective lens of ×50. If the Ni plating layer, which is the base layer, was exposed in any one of the three sets of test pieces (i.e., if peeling of the Ag plating was observed), it was judged as NG, and if the base layer was not observed in all three sets, it was judged as Good. If it is difficult to determine whether the Ni plating layer is exposed or not, it can be confirmed with an EPMA (electron probe microanalyzer).

[0117] As a result of the above evaluation, all three sets of test pieces were rated as "Good", indicating that the heat-resistant adhesion was excellent.

[0118] In addition, only in Example 1, the heat-resistant adhesion was evaluated under the condition of maintaining the temperature at 200° C. for 1000 hours, and all three sets of test pieces were rated as Good, indicating that the heat-resistant adhesion was excellent.

[0119] (Vickers hardness) The Vickers hardness HV of the surface of the Ag-coated material was measured in accordance with JIS Z2244 by forming an indentation using a microhardness tester (HM-221 manufactured by Mitutoyo Corporation) with a load of 10 gf, a lowering time of 3 seconds, a holding time of 10 seconds, and a rising time of 3 seconds. The result was a Vickers hardness HV of 110. A Vickers hardness HV of 98 or more is expected to have good abrasion resistance.

[0120] (contact resistance) Two test pieces were cut out from the Ag-coated material, one of which was made into a flat test piece, and the other was embossed (embossed into a hemispherical shape with an inner R of 1.5 mm) to make an embossed test piece (indenter), and the convex part of the embossed test piece was brought into contact with the flat test piece under a load of 5 N, and the contact resistance was measured at a measurement current of 10 mA using a precision sliding tester CRS-G2050-DWA model manufactured by Yamazaki Seiki Kenkyusho Co., Ltd. The contact resistance was 0.4 mΩ.

[0121] (Wear resistance) Two test pieces were cut out from the Ag-coated material, one of which was made into a flat test piece, and the other was embossed (hammered into a hemispherical shape with an inner R of 1.5 mm) to make an embossed test piece (indenter). The convex part of the embossed test piece was brought into contact with the flat test piece under a load of 5 N, and the test piece was slid back and forth at a sliding speed of 1.67 mm / s and a sliding distance of 5 mm using a precision sliding tester CRS-G2050-DWA model manufactured by Yamazaki Seiki Kenkyusho Co., Ltd. After 10 sliding cycles, the copper base was checked for exposure and the number of cycles until the copper base was exposed was measured. As a result, the copper base was not exposed until 80 reciprocating sliding cycles, and the wear resistance was good.

[0122] [Example 2] An Ag-coated material consisting of four Ag plating layers was produced by the same manufacturing method as in Example 1, except that an Ag plating layer having a thickness of 2.5 μm was formed in the Ag plating step A, and an Ag plating layer having a thickness of 2.5 μm was formed in the Ag plating step B to form an Ag plating film having a total thickness of 10 μm. The Ag purity (concentration) of each of these Ag plating layers was 99.9 mass% or more. Moreover, similarly to Example 1, the ratio of the average crystal grain sizes of adjacent Ag-plated layers was 3 or more.

[0123] The bending workability of this Ag-plated material was evaluated in the same manner as in Example 1. As a result, no exposure of the base material was observed when the bending radius R was 1.0 mm, and the bending workability was good. Moreover, exposure of the base material was confirmed when the bending radius was 0.5 mm.

[0124] Moreover, when the heat-resistant adhesion was evaluated in the same manner as in Example 1, all three sets of test pieces were rated as Good, which was satisfactory.

[0125] [Example 3] An Ag-coated material consisting of four Ag plating layers was produced by the same manufacturing method as in Example 1, except that an Ag plating film having a total thickness of 5 μm was formed by forming an Ag plating layer having a thickness of 1 μm in Ag plating step A as the first layer from the material side, an Ag plating layer having a thickness of 1 μm in Ag plating step B as the second layer, an Ag plating layer having a thickness of 1 μm in Ag plating step A as the third layer, and an Ag plating layer having a thickness of 2 μm in Ag plating step B as the fourth layer. The purity (concentration) of Ag in each of these Ag plating layers was 99.9 mass% or more. Moreover, similarly to Example 1, the ratio of the average crystal grain sizes of adjacent Ag-plated layers was 3 or more.

[0126] The bending workability of this Ag-plated material was evaluated in the same manner as in Example 1. As a result, no exposure of the base material was observed when the bending radius R was 1.0 mm, and the bending workability was good. Moreover, exposure of the base material was confirmed when the bending radius was 0.5 mm.

[0127] Moreover, when the heat-resistant adhesion was evaluated in the same manner as in Example 1, all three sets of test pieces were rated as Good, which was satisfactory.

[0128] [Comparative Example 1] An Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 5 μm (by the "Ag plating step A") and the second, third and fourth Ag plating layers were not formed. In other words, the Ag coating was a single layer consisting of only the first layer.

[0129] When the surface of this Ag-coated material was evaluated in the same manner as in Example 1 for evaluating the crystal orientation, the preferred orientation plane was found to be the {111} plane.

[0130] The bending workability, heat-resistant adhesion, Vickers hardness, contact resistance, and wear resistance of this Ag-plated material were evaluated in the same manner as in Example 1. As a result, the bending workability was poor, with the base material being exposed at bending radii R of both 1.0 mm and 0.5 mm, and the heat-resistant adhesion was NG. In addition, the Vickers hardness HV was 140, the contact resistance was 0.6 mΩ, and the wear resistance was good, with the copper base material not being exposed even after 80 reciprocating sliding operations.

[0131] [Comparative Example 2] An Ag-plated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 5 μm by the "Ag plating step B" and the second, third and fourth Ag plating layers were not formed. In other words, the Ag coating was a single layer consisting of only the first layer.

[0132] When the surface of this Ag-coated material was evaluated in the same manner as in Example 1 for evaluating the crystal orientation, the preferred orientation plane was found to be the {100} plane.

[0133] The bending workability, heat-resistant adhesion, Vickers hardness, contact resistance, and wear resistance of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was good with no exposure of the base material when the bending radius R was 1.0 mm. Exposure of the base material was confirmed when the bending radius R was 0.5 mm. Also, the heat-resistant adhesion was NG. Also, the Vickers hardness HV was 90, the contact resistance was 0.2 mΩ, and the wear resistance was poor with the copper base material being exposed after 50 reciprocating sliding operations.

[0134] [Comparative Example 3] After Ag strike plating, the plated material was placed in an Ag plating solution containing 115 g / L potassium silver cyanide (KAg(CN)2), 60 g / L potassium cyanide (KCN), and 32 mg / L Se (selenium). The plated material was used as the cathode and an Ag electrode plate made of Ag with a purity of 99.99% by mass or more was used as the anode. The plated material was then stirred at 500 rpm with a stirrer at a solution temperature of 30°C and a current density of 2 A / dm 2 Under the above conditions, electroplating (Ag plating) was performed until the thickness of the Ag plating film reached 5 μm, followed by rinsing with water for 15 seconds and drying with air pressure from an air gun to obtain a first Ag plating layer, and an Ag-coated material was produced in the same manner as in Example 1, except that the second, third and fourth Ag plating layers were not formed. In other words, the Ag film was a single layer consisting of only the first layer.

[0135] In this specification, the step of forming this first Ag plating layer is referred to as the “Ag plating step C”.

[0136] When the surface of this Ag-coated material was evaluated in the same manner as in Example 1, the preferred orientation plane was found to be the {110} plane.

[0137] The bending workability, heat-resistant adhesion, and Vickers hardness of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was poor, with the substrate being exposed at both bending radii R of 1.0 mm and 0.5 mm, and the heat-resistant adhesion was NG. The Vickers hardness HV was 110.

[0138] [Comparative Example 4] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step B", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step A", and the third and fourth Ag plating layers were not formed. That is, the Ag coating was composed of two Ag plating layers.

[0139] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was good with no exposure of the base material when the bending radius R was 1.0 mm. However, exposure of the base material was confirmed when the bending radius R was 0.5 mm. Also, the heat-resistant adhesion was NG.

[0140] [Comparative Example 5] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step A", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step B", and the third and fourth Ag plating layers were not formed. That is, the Ag coating was composed of two Ag plating layers.

[0141] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was good with no exposure of the base material when the bending radius R was 1.0 mm. However, exposure of the base material was confirmed when the bending radius R was 0.5 mm. Also, the heat-resistant adhesion was NG.

[0142] [Comparative Example 6] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step C", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step B", and the third and fourth Ag plating films were not formed. That is, the Ag film was composed of two Ag plating layers.

[0143] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was good with no exposure of the base material when the bending radius R was 1.0 mm. However, exposure of the base material was confirmed when the bending radius R was 0.5 mm. Also, the heat-resistant adhesion was NG.

[0144] [Comparative Example 7] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step B", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step C", and the third and fourth Ag plating layers were not formed. That is, the Ag coating was composed of two Ag plating layers.

[0145] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was good with no exposure of the base material when the bending radius R was 1.0 mm. However, exposure of the base material was confirmed when the bending radius R was 0.5 mm. Also, the heat-resistant adhesion was NG.

[0146] [Comparative Example 8] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step C", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step A", and the third and fourth Ag plating layers were not formed. That is, the Ag coating was composed of two Ag plating layers.

[0147] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was poor, with the substrate being exposed at bending radii R of both 1.0 mm and 0.5 mm, and the heat-resistant adhesion was NG.

[0148] [Comparative Example 9] The Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step A", the second Ag plating layer was formed to a thickness of 2.5 μm by the "Ag plating step C", and the third and fourth Ag plating layers were not formed. That is, the Ag coating was composed of two Ag plating layers.

[0149] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was poor, with the substrate being exposed at bending radii R of both 1.0 mm and 0.5 mm, and the heat-resistant adhesion was NG.

[0150] [Comparative Example 10] An Ag-coated material was produced in the same manner as in Example 1, except that the first Ag plating layer was formed by the "Ag plating step C", the second Ag plating layer was formed by the "Ag plating step B", the third Ag plating layer was formed by the "Ag plating step C", and the fourth Ag plating layer was formed by the "Ag plating step B". That is, the Ag coating was made up of four Ag plating layers, each of which was 1.25 μm thick, with the total thickness of the entire Ag plating coating being 5 μm.

[0151] The average crystal grain size (area average grain size) of this Ag-coated material was measured in the same manner as in Example 1. As a result, the first layer was 0.213 μm, the second layer was 0.265 μm, the third layer was 0.119 μm, and the fourth layer was 0.251 μm from the side closest to the substrate. In other words, the ratio of the average crystal grain size of each adjacent layer was less than 3.

[0152] The bending workability and heat-resistant adhesion of this Ag-coated material were evaluated in the same manner as in Example 1. As a result, the bending workability was poor, with the substrate being exposed at bending radii R of both 1.0 mm and 0.5 mm, and the heat-resistant adhesion was NG.

[0153] Moreover, the purity (concentration) of Ag in the Ag plating layers of Comparative Examples 1 to 10 was all 99.9 mass % or more.

[0154] The manufacturing conditions and properties of the Ag-coated materials of these examples and comparative examples are shown in Table 1.

[0155] [Table 1]

[0156] As can be seen from Table 1, the Ag-coated material produced in Example 1 has good bending workability, abrasion resistance, and heat-resistant adhesion.

Claims

1. A material and an Ag-coated material having an Ag coating formed on the material, The Ag coating has an Ag layer in which Ag layers 1 and Ag layers 2 having average crystal grain sizes different from each other by three or more times are alternately laminated in four or more layers, the preferred orientation plane of the Ag layer 1 is a {111} plane, and the Ag layer 1 is made of Ag having a small average crystal grain size; 1. An Ag-coated material, wherein the preferred orientation plane of said Ag layer is a {100} plane, and said Ag layer is made of Ag having an average crystal grain size larger than that of said Ag layer.

2. 2. The Ag-coated material according to claim 1, wherein the Ag coating has an Ag layer in which the Ag layer 1 and the Ag layer 2 are alternately laminated from the side closer to the material.

3. 3. The Ag-coated material according to claim 2, wherein the average crystal grain size (area average grain size) of the Ag layer 1 is 0.2 μm or less.

4. 4. The Ag-coated material according to claim 2, wherein the average crystal grain size (area average grain size) of the Ag layer 2 is 0.3 μm or more.

5. The Ag-coated material according to any one of claims 2 to 4, wherein the Ag layer 1 has a thickness of 0.5 to 5 µm.

6. The Ag-coated material according to any one of claims 2 to 5, wherein the Ag layer 2 has a thickness of 0.5 to 5 µm.

7. 7. The Ag-coated material according to claim 2, wherein the outermost layer of the Ag-coated material is composed of the Ag layer 2.

8. 8. The Ag-coated material according to claim 1, further comprising a base layer made of Ni formed between the material and the Ag coating.

9. The Ag-coated material according to any one of claims 1 to 8, characterized in that the material is made of Cu or a Cu alloy.

10. The Ag-coated material according to any one of claims 1 to 9, characterized in that the Ag-coated material has a Vickers hardness HV of 100 or more.

11. The method includes a step of forming an Ag coating on a material by alternately laminating four or more Ag layers 1 and Ag layers 2 having average crystal grain sizes that differ from each other by three times or more, The preferred orientation plane of the Ag layer 1 is the {111} plane, and the Ag layer 1 is made of Ag having a small average crystal grain size, A method for producing an Ag-coated material, characterized in that the preferred orientation plane of the Ag layer is a {100} plane and the Ag layer is made of Ag having an average crystal grain size larger than that of the Ag layer.

12. 12. The method for producing an Ag-coated material according to claim 11, wherein the Ag layer 1 and the Ag layer 2 are alternately formed on the material from the side closest to the material.

13. 13. The method for producing an Ag-coated material according to claim 12, wherein the average crystal grain size (area average grain size) of the Ag layer 1 is set to 0.2 μm or less.

14. 14. The method for producing an Ag-coated material according to claim 12, wherein the average crystal grain size (area average grain size) of the Ag layer 2 is set to 0.3 μm or more.

15. The method for producing an Ag-coated material according to any one of claims 11 to 14, characterized in that the Ag layer 1 has a thickness of 0.5 to 5 µm.

16. The method for producing an Ag-coated material according to any one of claims 11 to 15, characterized in that the Ag layer 2 has a thickness of 0.5 to 5 µm.

17. The method for producing an Ag-coated material according to any one of claims 11 to 16, wherein the Ag layer 2 is formed as an outermost layer of the Ag-coated material.

18. The Ag layer 1 is Using Ag plating solution 1 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate, the solution temperature was 10 to 35°C, and the current density was 3 to 15 A / dm 2 The film is formed by electroplating under the following conditions: The Ag plating solution 1 is 80 to 130 g / L of silver; 60 to 160 g / L of potassium cyanide; The method for producing an Ag-coated material according to any one of claims 11 to 17, characterized in that the aqueous solution contains 50 to 80 mg / L of selenium.

19. The method for producing an Ag-coated material according to claim 18, characterized in that the selenium is 55 to 70 mg / L.

20. The product of the concentration of potassium cyanide in the Ag plating solution 1 and the current density is 840 g·A / L·dm 2 The method for producing an Ag-coated material according to claim 18 or 19, characterized in that the electroplating is carried out under the following conditions:

21. The Ag layer 2 is A silver plating solution 2 containing potassium silver cyanide, potassium cyanide, and potassium selenocyanate was used, and the solution temperature was 10 to 40° C., and the current density was 3 to 10 A / dm 2 The resulting product is formed by electroplating with The silver plating solution 2 is 80-110 g / L of silver; 70 to 160 g / L of potassium cyanide; The method for producing an Ag-coated material according to any one of claims 11 to 20, characterized in that the aqueous solution contains 1 to 15 mg / L of selenium.

22. The method for producing an Ag-coated material according to any one of claims 11 to 21, characterized in that an underlayer made of Ni is formed on the material, and the Ag coating is formed on the underlayer.

23. The method for producing an Ag-coated material according to any one of claims 11 to 22, characterized in that the material is made of Cu or a Cu alloy.

24. A terminal part, comprising the Ag-coated material according to any one of claims 1 to 10 as a constituent material.

Citation Information

Patent Citations

  • Silver-plated terminal for connector

    JP2008169408A

  • Silver plated material and production method of the same

    JP2010222617A

  • Silver plating material and production method therefor

    JP2013076127A

  • Silver plating material

    JP2013189680A

  • Silver plated laminate

    JP2014095139A